The Effect of Physical Activity and Fatigue on Kinesthetic and Proprioceptive Awareness - Turner, Donna J. (My University, 1983)
This study investigated the effect of walking and exercise to fatigue on kinesthetic and proprioceptive awareness of males in three different physical activity levels . The Ss (residents of La Crosse County) completed a questionnaire which was used to separate them in to 3 activity groups (lowly active N=17, moderately active N = 15, highly active N=15). Prior to testing, the Ss were taught a 90 degree knee joint angle with their dominant leg. The Ss were tested on 2 separate occasions, once with a walking exercise and once with a fatiguing isokinetic exercise on the Cybex 11 apparatus. Pre- and post-exercise angle measurements were recorded to determine accuracy in reproducing the 90 degree angle. An ANOVA with repeated measures was utilized to assess the difference in kinesthetic and proprioceptive awareness between the three physical activity groups for pre- and post-test scores of fatigue and walking exercises. Results of the analysis revealed that (1) regardless of treatment, subjects of all physical activity levels realize a decrease in accuracy during post-exercise angle measurements i n comparison with pre-exercise angle measurements, (2) exercising to fatigue does not cause a greater deficit in kinesthetic and proprioceptive awareness than does walking, (3) the level of usual physical activity of an individual does not affect kinesthetic and proprioceptive awareness of the knee joint.
Keywords: Exercise --Psychological aspects; Exercise --Physiological aspects